TRIDAX PROCUMBENS MEDICINE FOR LIFE: AN OVERVIEW - ATISH K MALDHURE (International Journal of Pharma and Bio Sciences, 2015)
Nature has been a source of medicinal agents for thousands of years and an impressive numbers of modern drugs have been isolated from natural resources. Tridax procumbens Linn (Family –Asteraceae common name- Dhaman grass) is a common herb found in India. Tridax procumbens is well known Ayurvedic, ethino-botanical and unani medicinal plant. Pharmacological studies have shown that Tridax procumbens possess properties like anti-inflammatory, hepatoprotective, wound heal, antimicrobial, antiseptic, hypotensive and bradycardiac effects. The whole plant was reported to treat various elements, such as dysentery, diarrhea and preventing hair loss. These properties are mainly due to many active phytochemicals including the presence of carbohydrates, proteins, tannins, steroids, alkaloids, dexamethasone, luteoline, glucolureolin, b--silosterol, flaone, glycoside and quercetin in this plant.